Quantification of Chlorogenic Acid and Vanillin from Coffee Peel Extract and its Effect on α-Amylase Activity, Immunoregulation, Mitochondrial Oxidative Stress, and Tumor Suppressor Gene Expression Levels in H2O2-Induced Human Mesenchymal Stem Cells - Khalil Alyahya, Heba; Subash-Babu, Pandurangan; Mohammad Salamatullah, Ahmad; Hayat, Khizar; Albader, Nawal; Alkaltham, Mohammed Saeed; Ahmed, Mohammed Asif; Arzoo, Shaista; Bourhia, Mohammed (Frontiers in Pharmacology, 2021)
Abstract: Background: Polyphenols and flavonoid-rich foods help in arresting ROS development and protect DNA from oxidative damage. Recently coffee peel preparations are consumed as beverage, but its total polyphenol or flavonoid content and effect on oxidatively stressed hMSCs is poorly understood. Method: We prepared hot water extracts of coffee peel (CPE), further the amount of total polyphenol and flavonoid were quantified using HPLC analysis. In addition, the CPE have been studied for α-amylase inhibitory effect and beneficial effect in oxidative stress-induced human mesenchymal stem cells (hMSCs). Results: The obtained results enlighten that the availability of CGA, vanillin and salicylic acid level in CPE is more favorable on enhancing cell growth, nuclear integrity, and mitochondrial efficiency was confirmed by propidium iodide staining and JC-1 staining. CPE treatment to hMSCs for 48 hr, reduced oxidative stress by decreasing mRNA expression levels of LPO, NOX-4 and increasing antioxidant CYP1A, GSH, GSK-3β, GPX mRNA expressions. A decreased pro-inflammatory (TNF-α, NF-κβ, IL-1β, TLR-4) and increased tumor suppressor genes (except Bcl-2) such as, Cdkn2A, p53 expressions has been observed. Conclusion: The availability of CGA in coffee peel effectively reduced mitochondrial oxidative stress, pro-inflammatory, and increased tumor suppressor genes.